2016
DOI: 10.1039/c6cp06722k
|View full text |Cite
|
Sign up to set email alerts
|

Simple realization of efficient barrier performance of a single layer silicon nitride film via plasma chemistry

Abstract: Due to the problem of degradation by moisture or oxygen, there is growing interest in efficient gas diffusion barriers for organic optoelectronic devices. Additionally, for the continuous and long-term operation of a device, dedicated flexible thin film encapsulation is required, which is the foremost challenge. Many efforts are being undertaken in the plasma assisted deposition process control for the optimization of film properties. Control of the plasma density along with the energy of the principal plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…24 Additionally, SiN x C y and SiN x coatings are used or suggested as passivation layers in flexible electroluminescent devices. 25,26 It should also be noted that amorphous hydrogenated SiC x O z thin films are the subject of intense exploration as potential candidates for optoelectronic devices, due to their appealing photoluminescence characteristics. These include both white emission as well as emission in the blue at the highly desirable 1540 nm optical wavelength, when doped with erbium (Er).…”
mentioning
confidence: 99%
“…24 Additionally, SiN x C y and SiN x coatings are used or suggested as passivation layers in flexible electroluminescent devices. 25,26 It should also be noted that amorphous hydrogenated SiC x O z thin films are the subject of intense exploration as potential candidates for optoelectronic devices, due to their appealing photoluminescence characteristics. These include both white emission as well as emission in the blue at the highly desirable 1540 nm optical wavelength, when doped with erbium (Er).…”
mentioning
confidence: 99%
“…To investigate the deposition processes many groups correlate plasma and thin film analysis to identify important growth species and growth mechanisms. For example, Lee et al analysed film formation of SiN films from a symmetric capacitively coupled plasma (CCP) discharge with significant ion energies in the range of 100 eV. The plasma composition has been evaluated by emission spectroscopy and the film properties by Fourier transform infrared spectroscopy and permeation measurement.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed connection between plasma properties and film formation is often performed by using line intensities from optical emission spectra that can be connected to a modeling of the emission spectra or to a global chemistry model of the plasma of interest …”
Section: Introductionmentioning
confidence: 99%
“…However, as encapsulation materials, glass and metal lids are not suitable for transparent and flexible OLEDs. In response, extremely advanced inorganic films with various densities have been widely investigated as a highly efficient barrier, such as SiN x , Al x O y , SiO 2 , and so forth, deposited by plasma-enhanced chemical vapor deposition (PECVD), thermal and atomic layer deposition (ALD), and magnetron sputtering. So far, ALD is considered as the most efficient technique for achieving an exceedingly dense inorganic layer such as Al 2 O 3 because ALD deposits very thin, dense, and conformal films at low temperature (<100 °C) via control of the thickness and reaction cycles, and most recent research has reported that ultrahigh barrier (UHBs) films, defined as films having a lower WVTR of ∼10 –6 g/m 2 /day, have been successfully fabricated by adopting ALD (Table S1). The ALD process is, however, not cost-effective because of the use of an expensive vacuum process and is also not highly productive because of quite a low deposition rate .…”
Section: Introductionmentioning
confidence: 99%